Perancangan Sistem Online Monitoring Pembebanan Transformator Distribusi Menggunakan Mikrokontroller - Gunadin, Indar Chaerah; Herianto, Herianto; Bahtiar, Zity Aida; Hizbullah, Muhammad Al Izza (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Electric energy is basically one of the main needs used in various activities in the community. In the distribution of electricity energy is required a reliable system so that the continuity of electricity energy that reaches consumers can be guaranteed well. One of the systems that needs to be maintained is the system related to distribution in addition to transmission and power generation systems. Reliability and quality of power must be maintained properly. Transformer damage is usually affected by overload which can harm the transformer itself as well as transformer insulation. A hot transformer can cause a short circuit that can cause the transformer to explode, so that the damage to the transformer can shorten the life of use both in terms of tools and oil. Electricity monitoring system has been widely implemented with the installation of electric measuring instruments on the transformer panel before entering the load. This research aims to build a prototype transformer monitoring module in real time based on the Internet of Things. This research is in line with Unhas research plan related to innovations in the field of Energy and the development of smart grid systems that can optimize the utilization of various new and renewable sources that vary, while being able to control the efficient use patterns of electricity energy on the downstream side through the protocol of informatics technology systems that have advanced today